Inflammation, Cancer and Immunity—Implication of TRPV1 Channel - Bujak, Joanna Katarzyna; Kosmala, Daria; Szopa, Iwona Monika; Majchrzak, Kinga; Bednarczyk, Piotr (Frontiers in Oncology, 2019)
Process of inflammation and complex interactions between immune and cancer cells within tumor microenvironment are known to drive and shape the outcome of the neoplastic disease. Recent studies increasingly show that ion channels can be used as potential targets to modulate immune response and to treat inflammatory disorders and cancer. The action of both innate and adaptive immune cells is tightly regulated by ionic signals provided by a network of distinct ion channels. TRPV1 channel, known as a capsaicin receptor, was recently documented to be expressed on the cells of the immune system but also aberrantly expressed in the several tumor types. It is activated by heat, protons, proinflammatory cytokines and associated with pain and inflammation. TRPV1 channel is not only involved in calcium signaling fundamental for many cellular processes but also takes part in cell-environment crosstalk influencing cell behavior. Furthermore, in several studies, activation of TRPV1 by capsaicin was associated with anti-cancer effects. Therefore, TRPV1 provides a potential link between the process of inflammation, cancer and immunity and offers new treatment possibilities. Nevertheless, in many cases, results regarding TRPV1 are contradictory and need further refinement. In this review we present the summary of the data related to the role of TRPV1 channel in the process of inflammation, cancer and immunity, limitations of the studies and directions for future research.